(untitled) (Indo-Fintech Intellectuals: Journal of Economics and Business, 2022)
This research is an evaluation of the management of the marketing strategy for new student admissions at AMIK Bina Sriwijaya Palembang which is based on the decline in student admissions from 2019-2022. The purpose of this study is to identify the problems faced by AMIK Bina Sriwijaya in increasing new student admissions for the 2022-2023 academic year. This research method is qualitative descriptive with an indicator approach to marketing mix, service quality, physical form and using the fishbone diagram method using data collection methods with deep interviews and observations. The results showed that 7 main variables can be concluded that there is a problem of decreasing the number of students at AMIK Bina Sriwijaya from year to year with the main problems as follows: (1) The student admission system is still manual; (2) Does not have cooperation with related parties regarding the financial administration process; (3) The promotion carried out by AMIK Bina Sriwijaya Palembang is still based on the promotion manual; (4) Content that features in promotions; (5) The selling power of AMIK Bina Sriwijaya which is superior; (6) The curriculum and quality of lecturers, lecturers who make the backbone of D3 Computer Science lectures have not met expectations; (7) Facilities and supporting facilities for lectures at AMIK Bina Sriwijaya are inadequate.